A remarkable new species of Asuridia Hampson, 1900 from China (Lepidoptera: Erebidae: Arctiinae: Lithosiini) - Huang, Si-Yao; Volynkin, Anton V.; Wang, Min; Fan, Xiao-Ling (Zootaxa, 2020)
An unique new species of the genus Asuridia is described from Hubei Province, Central China, viz. Asuridia nigrubra Huang, Volynkin & Wang sp. nov. An annotated checklist of Asuridia from China is also provided. Adults and genitalia of related and externally similar species are illustrated.